One-Year Prospective Study Evaluating the Role of the WALANT Technique in Managing Upper Limb Trauma in the Emergency Room: Assessing WALANT in Emergency Management of Upper Limb Trauma: A Prospective Study - Barchah, Oussama; Ait Rahou, Marouane; Achkoun, Abdessalam; El Haoury, Hanane; Madhar, Mohammed; Chafik, Rachid; Najeb, Youssef (International Journal of Innovative Research in Medical Science, 2023)
Background: WALANT (Wide Awake Locale Anesthesia No Tourniquet) is a technique recently developed by Lalonde. It has allowed surgeons to perform more procedures with a remarkable time grain and to reduce the cost. The objective of our study is to evaluate the interest of this technique in the management of upper limb trauma in the emergency room. Results: The study included 36 patients, 14 fractures and 22 wounds. The average waiting time in the emergency room was 82.9 minutes, the average time between anesthesia and incision was 37 minutes, and the average duration of the procedure was 37 minutes. Three patients whose procedure was prolonged required additional anesthetic, and no patient required sedation or general anesthesia. None of the patients required the use of a tourniquet. No complications were reported in these patients. 92% of patients were satisfied. Discussion: WALANT makes it possible to perform surgical procedures using only lidocaine and adrenaline in combination with bicarbonate and saline. The long-standing dogma about the involvement of adrenaline in ischemic necrosis of the fingers has been reconsidered by several authors. Several advantages have been reported in the various publications. This concerns the patient, the surgeon and the health care system. Thus, it allows to improve the result in tendon repairs and to verify the stability of the osteosynthesis intraoperatively. Conclusion: WALANT presented a solution to the shortage of medical staff during the COVID-19 pandemic by reducing the risk of contagiousness through the reduction of the number of staff in the OR and shortening the hospital stay.